Public Distrust and Environmental Citizenship: Primary Impetuses of Radical Protest in Bima District, 2011-2012 - Rahmad Hidayat (Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
This article aims to show how the social movement was conducted in the framework of claiming a number of aspects of citizenship, especially environmental rights and political participation, to the local government. The refusal of FRAT Bima over the extractive policy of the Government of Bima District during 2011-2012 becomes a reflective context of the type of social movement with such a framework. This social protest should be explored further because it used acts of vandalism on some public facilities as the chosen way to fight against the environmental and political injustices. Through a case study, the author aims to explore the sequence of repertoires which were applied sequentially by FRAT Bima’s social protest as well as to examine its linkage with environmental citizenship and public distrust. Despite being closely related to citizens' awareness about environmental citizenship, the occurrence of this anarchist movement was also triggered by the low level of "formal legitimacy" of the local government as a seed of public distrust towards the intentions of environmental governance policy that was about to be applied to make the agricultural land owned by villagers as the site of a certain project of mineral extraction. The lack of the government’s formal legitimacy, which was supported by the growing awareness of environmental citizenship, has led the sequential application of conventional and non-conventional strategies in the demands articulation of FRAT Bima. This sequence of repertoires was held due to the low-level of government's responsiveness in accommodating the public claims about the cancellation of an undemocratic environmental policy.